2022
DOI: 10.1002/cncr.34210
|View full text |Cite
|
Sign up to set email alerts
|

Venous‐thromboembolism and associated health care utilization in elderly patients with diffuse large B cell lymphoma

Abstract: BACKGROUND:Patients with lymphoma have an increased risk of venous thromboembolism (VTE). The authors examined the risk of VTE and subsequent health care utilization in elderly patients with diffuse large B cell lymphoma (DLBCL). METHODS: A total of 5537 DLBCL patients ≥66 years old enrolled in Medicare from the Surveillance, Epidemiology, and End Results registry and a noncancer control group of Medicare beneficiaries (n = 5537) were identified. Cumulative incidence function to examine the risk of VTE 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Similarly, Santi et al showed that DLBCL patients had a higher risk of experiencing VTE (SHR: 3.42 [1.32–8.84]; p = 0.011) compared with those with FL 30 . VTE history was confirmed as prognostic factors in comparable lymphoma studies 7,31–33 . Recent hospitalization and history of paralysis/immobility were other well‐known predictors for VTE, 14,34–36 but they have not been explored in the lymphoma setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Santi et al showed that DLBCL patients had a higher risk of experiencing VTE (SHR: 3.42 [1.32–8.84]; p = 0.011) compared with those with FL 30 . VTE history was confirmed as prognostic factors in comparable lymphoma studies 7,31–33 . Recent hospitalization and history of paralysis/immobility were other well‐known predictors for VTE, 14,34–36 but they have not been explored in the lymphoma setting.…”
Section: Discussionmentioning
confidence: 99%
“…30 VTE history was confirmed as prognostic factors in comparable lymphoma studies. 7,[31][32][33] Recent hospitalization and history of paralysis/immobility were other well-known predictors for VTE, 14,34-36 but they have not been explored in the lymphoma setting. Also, the differential risk associated with chemotherapy versus targeted therapy has not been systematically incorporated into lymphoma-specific RAMs, although several studies have reported the increased VTE risk associated with cytotoxic therapy, 7,31,37,38 while one study has reported a lower incidence of VTE among patients receiving ibrutinib.…”
Section: Stratified Analyses and Comparisons With Other Modelsmentioning
confidence: 99%